Cdkn2a is an atherosclerosis modifier locus that regulates monocyte/macrophage proliferation - Kuo, Chao-Ling (2011)
OBJECTIVE: Common genetic variants in a 58-kilobase region of chr 9p21, near the CDKN2A/CDKN2B tumor suppressor locus, are strongly associated with coronary artery disease. However, the underlying mechanism of action remains unknown. METHODS AND RESULTS: We previously reported a congenic mouse model harboring an atherosclerosis susceptibility locus and the region of homology with the human 9p21 locus. Microarray and transcript-specific expression analyses showed markedly decreased Cdkn2a expression, including both p16(INK4a) and p19(ARF), but not Cdkn2b (p15(INK4b)), in macrophages derived from congenic mice compared to controls. Atherosclerosis studies in subcongenic strains revealed genetic complexity and narrowed one locus to a small interval including Cdkn2a/b. Bone marrow (BM) transplantation studies implicated myeloid lineage cells as the culprit cell type rather than resident vascular cells. To directly test the role of BM-derived Cdkn2a transcripts in atherogenesis and inflammatory cell proliferation, we performed a transplantation study utilizing Cdkn2a(+/−) cells in the Ldlr(−/−) mouse model. Cdkn2a-deficient BM recipients exhibited accelerated atherosclerosis, increased Ly6C(hi) pro-inflammatory monocytes and increased monocyte/macrophage proliferation compared to controls. CONCLUSIONS: These data provide a plausible mechanism for accelerated atherogenesis in susceptible congenic mice, involving decreased expression of Cdkn2a and increased proliferation of monocyte/macrophages, with possible relevance to the 9p21 human locus.